Hadits-hadits yang menjadi sumber tasawuf - Aziz, Al Fira Elisa (Maliki Interdisciplinary Journal, 2024)
This study aims to explain how hadiths serve as the primary source o Sufi teachings and their classifications. Understanding hadiths in Sufism is approached in two ways : textual and contextual. The textual approach interprets the meaning of hadiths according to their original text without considering the historical background, while the contextual approach involves interpretation that considers the context of time, situation, and its relevance to current conditions. This study is expected to help readers understand the source of Sufi studies, particularlt hadiths as the main source of Sufism.